Suppression of tumor necrosis factor-alpha-induced neutrophil adherence responses by essential oils - Shigeru Abe; Naho Maruyama; Kazumi Hayama; Hiroko Ishibashi; Shigeharu Inoue; Haruyuki Oshima; Hideyo Yamaguchi (Mediators of Inflammation)
Background: In aromatherapy, essential oils are used as anti-inflammatory remedies, but experimental studies on their action mechanisms are very limited.